Reação de estado sólido em filmes multicamadas de Fe-Hf - Honda, Enio Yoiti (2001)
Fe-Hf thin multilayered films, deposited by electran-beam, were annealed by 1h and 3h, at temperatures of 350°C and 500°C. The phases farmed by Salid State Reaction, with overall composition af Fe0,67Hf0,33 and Fe0,50Hf0,50 were analysed by Rutherford Backscattering Spectroscopy (RBS), Magnetization (VSM) and M¨pssbauer Spectroscopy (CEMS). The results reveal that the first reacted phase is an amorphous phase, with composition near to 50%at.Fe. The crystalline phase Fe2Hf was also identified in the iron-rich sample annealed at 500°C by 3h. It was shown, as already observed in others binary Fe-MT systems, that the sequence of phase formation depends, fundamentally, on the composition of the as-deposited multilayer and on the annealing temperature. A schematic diagram of Gibbs Free Energy was proposed in order to explain the experimental results.